The Interplay Between Cervicovaginal Microbial Dysbiosis and Cervicovaginal Immunity - Wang, Ya; Wang, Xiaoli; Zhu, Meiling; Ge, Li; Liu, Xiaochen; Su, Kaikai; Chen, Zhengzheng; Zhao, Weidong (Frontiers in Immunology, 2022)
The cervicovaginal microbiota plays a key role in the health and reproductive outcomes of women. Epidemiological studies have demonstrated the significant impact of cervicovaginal communities on reproductive health, although key mechanistic questions regarding these effects remain unanswered. Therefore, there is significant research interest in the role of the microbiota in health and disease and understanding the interplay between the immune system and the reproductive tract in women. Here, we review existing literature relating to the potential mechanisms underlying the interaction between vaginal microbes and the immune system; we also describe the composition and function of the microbiome and explain the mechanisms underlying the interactions between these microbial communities and various aspects of the immune system. Finally, we also discuss the diseases that are caused by disorders of the reproductive tract.